Mechanical and microstructural characterization of Al7075/SiC nanocomposites fabricated by dynamic compaction - Atrian, A.; Majzoobi, G. H.; Enayati, M. H.; Bakhtiari, H. (International journal of minerals, metallurgy and materials, 2014)
This paper describes the synthesis of Al7075 metal matrix composites reinforced with SiC, and the characterization of their microstructure and mechanical behavior. The mechanically milled Al7075 micron-sized powder and SiC nanoparticles are dynamically compacted using a drop hammer device. This compaction is performed at different temperatures and for various volume fractions of SiC nanoparticles. The relative density is directly related to the compaction temperature rise and indirectly related to the content of SiC nanoparticle reinforcement, respectively. Furthermore, increasing the amount of SiC nanoparticles improves the strength, stiffness, and hardness of the compacted specimens. The increase in hardness and strength may be attributed to the inherent hardness of the nanoparticles, and other phenomena such as thermal mismatch and crack shielding. Nevertheless, clustering of the nanoparticles at aluminum particle boundaries make these regions become a source of concentrated stress, which reduces the load carrying capacity of the compacted nanocomposite.